Pembekalan dan Peningkatan Motivasi Berprestasi Atlit Pemula SH Terate Ranting Saradan - Asyarin Hayau Lailin, Moch. Ichdah; Zusyana Dewi, Ratnaningrum (Jurnal Kabar Masyarakat, 2025)
This community service program aims to increase the motivation of novice athletes to achieve in the SH Terate Ranting Saradan organization, Madiun Regency. Program implementation uses various methods, such as observation, training, lectures, demonstrations, and consultations. Initial observations were conducted to identify participants' needs and challenges, especially in understanding the importance of achievement motivation and physical and mental readiness. The training is designed systematically, combining theoretical understanding through lectures and direct practice through demonstrations and individual consultation sessions. The program results show a significant increase in participants' abilities, especially in understanding achievement and competitive readiness. As proven through practical evaluations, as many as 80% of participants showed improved performance after participating in this program. Apart from that, this program also strengthens the values ​​of sportsmanship and appreciation for pencak silat as the nation's cultural heritage. With a structured and participation-based approach, this program is hoped to become a model for pencak silat training for other branches. Not only does this program equip participants with sports skills, but it also contributes to preserving pencak silat as part of Indonesia's cultural identity.